Short-chain fatty acids in breast milk and their relationship with the infant gut microbiota - Xi, Menglu; Yan, Yalu; Duan, Sufang; Li, Ting; Szeto, Ignatius Man-Yau; Zhao, Ai (Frontiers in Microbiology, 2024)
Introduction The short-chain fatty acids (SCFAs) contained in breast milk play a key role in infant growth, affecting metabolism and enhancing intestinal immunity by regulating inflammation. Methods In order to examine the associations between the microbiota and SCFA levels in breast milk, and explore the roles of SCFAs in regulating the infant gut microbiota, we enrolled 50 paired mothers and infants and collected both breast milk and infant fecal samples. Breast milk SCFA contents were determined by UPLC-MS, and whole genome shotgun sequencing was applied to determine the microbial composition of breast milk and infant feces. The SCFA levels in breast milk were grouped into tertiles as high, medium, or low, and the differences of intestinal microbiota and KEGG pathways were compared among groups. Results The results demonstrated that breast milk butyric acid (C4) is significantly associated with Clostridium leptum richness in breastmilk. Additionally, the specific Bifidobacterium may have an interactive symbiosis with the main species of C4-producing bacteria in human milk. Women with a low breast milk C4 tertile are associated with a high abundance of Salmonella and Salmonella enterica in their infants' feces. KEGG pathway analysis further showed that the content of C4 in breast milk is significantly correlated with the infants' metabolic pathways of lysine and arginine biosynthesis. Discussion This study suggests that interactive symbiosis of the microbiota exists in breast milk. Certain breast milk microbes could be beneficial by producing C4 and further influence the abundance of certain gut microbes in infants, playing an important role in early immune and metabolic development.